Accounting standard precision and incentive for revenue management / Lim Ying Zhee - Lim, Ying Zhe (2016)
Despite the fact that accounting standards tend to be used as tools to legitimise questionable accounting decisions, it is essential to ensure that the standards provide a proper level of prescription for guiding managers’ financial reporting decisions and minimising aggressive reporting. Drawing inferences from the newly issued IFRS 15, this study examined the issues related to the inclusion of indicators in a set of principle-based standards. In addition, taking into consideration that incentives play an important role in the financial reporting process, given different levels of accounting standard precision (principle, principle with indicators), the present study examined the moderating effect of different reported revenue trends (increasing, decreasing, and volatile) and credit rating downgrade types (notch, category) on revenue management through a 2x3x2 between subject experiment. The empirical results of the experiment show that the inclusion of indicators in a principle-based standard can constrain managers’ revenue management intentions. When a standard is less precise, the incentives of reported revenue trends and credit rating downgrades will moderate the manner in which the standard will be interpreted, making it easier for managers to engage in revenue management. The findings of this study not only extend the literature in the field of accounting standard precision and incentives, and their effects on aggressive reporting, they also provide useful insights for standard setters engaged in revisiting accounting standards in use.